SPRINGS CONSERVATION ENGINEERING IN SENGI VILLAGE, DUKUN DISTRICT, MAGELANG REGENCY - Johan Danu Prasetya; Taufik Fatkur Rohman; Herwin Lukito (Techno LPPM, 2021)
Problems related to the sustainability of water resources often occur, both from the impact of the erratic change of seasons, the reduction in water catchment areas, to the many cases of water pollution in Indonesia. However, the main problem of all that lies in the community itself where awareness of the importance of conservation and management of water resources is still low. The selected study was located in Sengi Village, Dukun District, Magelang Regency, Central Java Province. The local community utilizes springs as the main water supply source, but the water management carried out by the community is still classified as less than optimal. Therefore, there is a need for conservation efforts so that the sustainability and function of these springs can be maintained properly. The results of the study showed that spring conservation was carried out by constructing a spring reservoir with a volume of 2 m3 for spring 1 and a spring reservoir with a volume of 5 m3 for spring 2. In addition, a social approach to the community in the local area regarding the preservation of the condition of the springs was also carried out. affixed area